2017
DOI: 10.1111/jfbc.12419
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acids alleviate high-fat and high-fructose diet-induced metabolic disorders in rats

Abstract: Phenolic acids are naturally occurring compounds with meritorious physiological activities. The purpose of this study was to compare the ameliorative effects of six common phenolic acids on diet‐induced metabolic syndrome (MS) in rats. SD rats were fed with high‐fat and high‐fructose diet supplemented with equimolar concentration of individual phenolic acids for 13 weeks. Results showed that different phenolic acids ameliorated MS through different ways. Compared with other phenolic acids, caffeic acid exerted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…After prolonged ingestion of HFFD, an increasing number of people suffer from MetS, diabetes mellitus, cardiovascular disease, and other chronic diseases, which are closely linked to HUA ( 9 , 32 ). Under the circumstances of most drugs that show some side effects, dietary intervention derived from natural ingredients exhibits a great advantage ( 16 , 17 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After prolonged ingestion of HFFD, an increasing number of people suffer from MetS, diabetes mellitus, cardiovascular disease, and other chronic diseases, which are closely linked to HUA ( 9 , 32 ). Under the circumstances of most drugs that show some side effects, dietary intervention derived from natural ingredients exhibits a great advantage ( 16 , 17 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under the circumstances of most drugs that show some side effects, dietary intervention derived from natural ingredients exhibits a great advantage ( 16 , 17 , 34 ). Our team successfully established a MetS model using HFFD in vivo and reported that several polyphenols and polyunsaturated fatty acids could alleviate MetS ( 2 , 32 , 35 ). Ferulic acid, one of the phenolic acid compounds, possessed a beneficial function in regulating glucose and lipid metabolism, antioxidation, antiinflammation, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study using EA to treat an LPS-induced dopamine neuronal damage rat model, EA had a profound effect on protecting dopamine neurons via suppression of the microglial nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome signaling activation and reduction of proinflammatory cytokine (IL-1β, TNF-α, and IL-18) expression [ 62 ]. In another study of Sprague Dawley rats fed with a high-fat diet supplemented with equimolar concentrations of EA for 13 weeks, EA exhibited good anti-inflammatory performance, for example by reducing serum cytokines IL-6, IL-1β, and TNF-α [ 63 ]. Gallic acid (3,4,5-trihydroxybenzoic acid, GA) has a wide range of antioxidant, anti-inflammatory, and antimicrobial properties [ 64 ].…”
Section: Anti-inflammatory Components Of Walnutsmentioning
confidence: 99%
“…4). It has been reported that its anti-inflammatory and antioxidant activity may ameliorate tissue damage and inflammation from oxidative stress or/and free radical accumulation that were implicated in hepatic injury as well as in hyperlipidemia [25,26].…”
Section: The Expression Level Of Ppar-α In Hepaticmentioning
confidence: 99%